Beyond green: Broad support for biodiversity in multicultural European cities. (March 2018) - Fischer, Leonie K.; Honold, Jasmin; Cvejić, Rozalija; Delshammar, Tim; Hilbert, Sven; Lafortezza, Raffaele; Nastran, Mojca; Nielsen, Anders Busse; Pintar, Marina; van der Jagt, Alexander P.N.; Kowarik, Ingo
Graphical abstract: Highlights: First international survey on biodiversity valuation in four urban greenspace types. Study couples biodiversity measures with sociocultural background variables. People prefer high plant species richness in urban greenspaces. Study demonstrates broad support for biodiverse, and not only green urban spaces. Results provide a social argument for a biodiversity-friendly urban development. Abstract: While urban growth contributes to the biodiversity crisis, biodiverse greenspaces within cities could support both human wellbeing and biodiversity conservation. Yet, urban greenspaces are under pressure due to the rapid densification of cities worldwide. Urban conservation policies thus need broad support, ideally from people with different sociocultural backgrounds. Whether urban residents prefer biodiverse over simply green spaces, however, largely remains an open question. We tested how diverse respondents ( N = 3716) from five European cities valued three levels of biodiversity (plant species richness) in four ubiquitous greenspace types. Our field survey revealed that biodiversity matters: People largely prefer higher plant species richness in urban greenspaces (i.e., parks, wastelands, streetscapes) and agree that higher plant species richness allows for more liveable cities. Despite variation across European cities, positive valuations of high plant species richness prevailed among different sociocultural groups, including people of migrant background. The results of this study can thus support policies on a biodiversity-friendly development and management of urban greenspaces by highlighting social arguments for integrating biodiversity into urban development plans.